2006
DOI: 10.1055/s-2006-924233
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity Indices: a Proposal of Cut-Off Points for Simple Identification of Insulin-Resistant Subjects

Abstract: Demanding measurement of insulin sensitivity using clamp methods does not simplify the identification of insulin resistant subjects in the general population. Other approaches such as fasting- or oral glucose tolerance test-derived insulin sensitivity indices were proposed and validated with the euglycemic clamp. Nevertheless, a lack of reference values for these indices prevents their wider use in epidemiological studies and clinical practice. The aim of our study was therefore to define the cut-off points of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 28 publications
5
121
4
Order By: Relevance
“…The biochemical marker of this dysfunctional state was reflected by an increased HOMA-IR, a validated index of insulin sensitivity. 18 To our knowledge, no data on the relationship between cannabis use and ED with documented vascular (penile) and endothelial (brachial) arterial damage have been reported earlier.…”
Section: Discussionmentioning
confidence: 87%
“…The biochemical marker of this dysfunctional state was reflected by an increased HOMA-IR, a validated index of insulin sensitivity. 18 To our knowledge, no data on the relationship between cannabis use and ED with documented vascular (penile) and endothelial (brachial) arterial damage have been reported earlier.…”
Section: Discussionmentioning
confidence: 87%
“…However, Moltz showed recently that it is possible to determine IR using defined cut off points for glucose (102 mg/dl) and insulin (13 mU/ml) when screening for the metabolic syndrome (30). Insulin sensitivity indices that use fasting glucose and insulin values may not provide greater objectivity in assessing insulin resistance than fasting values for glucose and insulin itself (31)(32)(33). The advantage of using GIR, HOMA-IR, HOMA-B, and QUICKI may therefore be questionable.…”
Section: Eumenorrhea (Nz44)mentioning
confidence: 99%
“…The advantage of using GIR, HOMA-IR, HOMA-B, and QUICKI may therefore be questionable. The Matsuda ISI is the only index that incorporates 1-and 2-h levels for OGTT into the calculation model, and it has been reported that the Matsuda ISI is best able to predict the risk of insulin resistance and provides the best relative sensitivity and specificity rates in comparison with other markers (31,33). Recently, reference values have also been established for the Matsuda ISI in order to distinguish between patients with insulin resistance and those who are insulin sensitive (31).…”
Section: Eumenorrhea (Nz44)mentioning
confidence: 99%
See 2 more Smart Citations